Impact of the CYP2C8 *3 polymorphism on the drug–drug interaction between gemfibrozil and pioglitazone. (14th December 2012) - Aquilante, Christina L.; Kosmiski, Lisa A.; Bourne, David W. A.; Bushman, Lane R.; Daily, Elizabeth B.; Hammond, Kyle P.; Hopley, Charles W.; Kadam, Rajendra S.; Kanack, Alexander T.; Kompella, Uday B.; Le, Merry; Predhomme, Julie A.; et al.
<x xml:space="preserve">Abstract</x> WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT A drug–drug interaction exists between gemfibrozil (CYP2C8 inhibitor) and pioglitazone (CYP2C8 substrate), whereby gemfibrozil increases pioglitazone plasma exposure. Substantial interindividual variability exists in the pharmacokinetic magnitude of this drug–drug interaction. CYP2C8*3 is associated with increased metabolism and decreased plasma exposure of pioglitazone. Polymorphisms in CYP metabolizing enzyme genes, namely CYP2C19 and CYP2D6, have been shown to influence the magnitude of inhibitory drug–drug interactions. However, the extent to which CYP2C8 polymorphisms (e.g. CYP2C8*3) affect the interaction between gemfibrozil and pioglitazone is not known. WHAT THIS STUDY ADDS The CYP2C8*3 allele influences pharmacokinetic variability in the drug–drug interaction between gemfibrozil and pioglitazone. CYP2C8*3 carriers experienced a larger relative increase in pioglitazone plasma exposure following gemfibrozil administration than wild‐type homozygotes. Consideration should be given to the contribution of polymorphic CYP2C8 alleles to interindividual variability in the pharmacokinetic magnitude of CYP2C8‐mediated drug–drug interactions. AIM The objective of this study was to determine the extent to which the CYP2C8*3 allele influences pharmacokinetic variability in the drug–drug interaction between gemfibrozil (CYP2C8 inhibitor) and pioglitazone (CYP2C8 substrate). METHODS In this randomized, two phase crossover study, 30 healthy Caucasian subjects were enrolled based on CYP2C8*3 genotype (n= 15, CYP2C8*1/*1; n= 15, CYP2C8*3 carriers). Subjects received a single 15 mg dose of pioglitazone or gemfibrozil 600 mg every 12 h for 4 days with a single 15 mg dose of pioglitazone administered on the morning of day 3. A 48 h pharmacokinetic study followed each pioglitazone dose and the study phases were separated by a 14 day washout period. RESULTS Gemfibrozil significantly increased mean pioglitazone AUC(0, ∞) by 4.3‐fold (P < 0.001) and there was interindividual variability in the magnitude of this interaction (range, 1.8‐ to 12.1‐fold). When pioglitazone was administered alone, the mean AUC(0, ∞) was 29.7% lower (P= 0.01) in CYP2C8*3 carriers compared with CYP2C8*1 homozygotes. The relative change in pioglitazone plasma exposure following gemfibrozil administration was significantly influenced by CYP2C8 genotype. Specifically, CYP2C8*3 carriers had a 5.2‐fold mean increase in pioglitazone AUC(0, ∞) compared with a 3.3‐fold mean increase in CYP2C8*1 homozygotes (P= 0.02). CONCLUSION CYP2C8*3 is associated with decreased pioglitazone plasma exposure in vivo and significantly influences the pharmacokinetic magnitude of the gemfibrozil–pioglitazone drug‐drug interaction. Additional studies are needed to evaluate the impact of CYP2C8 genetics on the pharmacokinetics of other CYP2C8‐mediated drug–drug interactions.